1997
DOI: 10.1080/002075497195911
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of US- andforeign-owned firms: A new perspective on ISO 9000 implementation

Abstract: Responses from over 500 companies relating to their experiences with ISO 9000 implementation are presented. Companies were categorized according to ownership: U S-owned (Type U ) and foreign-owned (Type F ) manufacturing ® rms. The results reveal the importance and the dual role of documentation as a critical factor necessary to obtain ISO 9000 registration: (1) as the critical element requiring the highest level of eOE ort in the registration process; and (2) as one of the key potential barriers to successful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
1
10

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 0 publications
2
38
1
10
Order By: Relevance
“…Although there are many studies reporting expectations of increased market share and improved product quality from ISO 9000 implementation (for example, Ebrahimpour et al, 1997), there are much fewer empirical studies on the business performance benefits actually achieved. The UK research of Mann and Kehoe (1994) noted that quality certification was associated with improved business performance at the operational level.…”
Section: Iso 9000 Certification and Business Performancementioning
confidence: 99%
“…Although there are many studies reporting expectations of increased market share and improved product quality from ISO 9000 implementation (for example, Ebrahimpour et al, 1997), there are much fewer empirical studies on the business performance benefits actually achieved. The UK research of Mann and Kehoe (1994) noted that quality certification was associated with improved business performance at the operational level.…”
Section: Iso 9000 Certification and Business Performancementioning
confidence: 99%
“…Nonetheless, Ebrahimpour, Whithers andHikmet (1997) suggested that some firms have experience difficulties in conducting internal quality audits and, subsequently, in taking the required corrective actions. Sun and Cheng (2002) and Thomas and Webb (2003) have even questioned the costeffectiveness and feasibility of implementing ISO 9000 in small-to-medium enterprises (SMEs) in the European manufacturing sector.…”
Section: Research Hypothesesmentioning
confidence: 99%
“…Initial screening of the 2000 or so electronic search listings excluded materials that were not in peer-reviewed journals, followed by a relevance screening to exclude articles that did not explicitly measure business benefits or performance variables. At this stage it was found that there were many studies reporting expectations of increased market share and improved product quality from ISO 9001 implementation (Ebrahimpour et al, 1997), but there were less than 100 empirical studies on the business performance benefits actually achieved.…”
Section: Iso 9001 Quality Management and Performance Literaturementioning
confidence: 99%